1997
DOI: 10.1046/j.1523-1739.1997.95481.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Constraints Associated with the Use of Black Rhinos as an Umbrella Species for Desert Herbivores

Abstract: The numerous tactics used to conserve biodiversity include the designation of protected areas, political change, and research and education, the latter involving paradigms such as insular biogeography and the “umbrella species concept.” In Namibia lands removed from national park status in 1970 and currently under the jurisdiction of indigenous people now contain one of the few unfenced populations of black rhinos (Diceros bicornis) remaining in Africa. Theory predicts that the protection of umbrella species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Many of these species might also act as effective umbrella species, facilitating the conservation of their smaller brethren (Karanth 2003;Thorne et al 2006). Though large-bodied species are often useful umbrella species, this cannot always be assumed a priori; for example, Berger (1996) showed that black rhinoceros (Diceros bicornis) in Namibia, despite their large size, do not actually serve as umbrella species for smaller ungulates due to different seasonal distributions. Finally some research on large cats continues to generate extremely useful insights with broad applications.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these species might also act as effective umbrella species, facilitating the conservation of their smaller brethren (Karanth 2003;Thorne et al 2006). Though large-bodied species are often useful umbrella species, this cannot always be assumed a priori; for example, Berger (1996) showed that black rhinoceros (Diceros bicornis) in Namibia, despite their large size, do not actually serve as umbrella species for smaller ungulates due to different seasonal distributions. Finally some research on large cats continues to generate extremely useful insights with broad applications.…”
Section: Discussionmentioning
confidence: 99%
“…Species categorised as an umbrella require large areas of habitat for their survival and, therefore, by protecting their habitat, many other species will be protected [16,165], including those that share similar ecology [166,167] or those species more directly interacting with them [168]. However, the conservation of these other species is strongly dependent on the appropriate selection of the umbrella species [169,170].…”
Section: Eciton Army Ants As Umbrella Species In Neo-tropical Forestsmentioning
confidence: 99%
“…As a result of long‐distance movements, drought can increase the spatial heterogeneity in herbivore abundance, with individuals aggregated in areas less affected by drought (Pople et al, 2007). Alternatively, the demographic characteristics of megaherbivore populations, for example, high survival during drought, may buffer demographic variability in response to extreme weather events (Berger, 1997; Trimble et al, 2009). These relationships among resource availability, movement and local density are thus critical to understanding the response of megaherbivores to extreme weather events (Chamaillé‐Jammes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%